Cambodia in WTO : prospects and challenges - Dourng Kakada; Tang, John C.S.; Broustai, Joel Francois; Zimmermann, Willi; Government of France (Pathum Thani, Thailand : Asian Institute of Technology, 2004)
This research study analyses the prospects and challenges faced by Cambodian economy through assessment of selected sensitive industries and TRIPS-plus, when Cambodia becomes a full member of WTO. It provides a comprehensive research and attracts an attention of major stakeholders such as government, businessman, employees, experts, researchers and students. The selected three industries include rice, garment and tourism industry. There are some reasons for this selection. More than 80% of Cambodians are employed the agriculture of which 50% are in rice industry. The garment industry is a major source of employment creation, the main recipients of FDI, and foreign exchange earning; representing 77% of product exports and this industry will face a challenge of quotas elimination in early 2005. Tourism industry growths rapidly during recent year, and represents 15% of country's GDP in 2002. Moreover, the accepting of TRIPS-plus due to the pressure from other members will be the cost for Cambodia economy. The findings show that the main challenge for Cambodia comes from the supply side, while the government is trying to remove the trade constraints and to integrate itself in to regional and global trading systems such as WTO, ASEAN and Bilateral Agreements to explore demand in new markets. Finally, the research provides some recommendations to deal with these challenges and to meet these opportunities.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Research Studies Project Report (M.BA.) - Asian Institute of Technology, 2004
Keywords: World Trade Organization; Cambodians -- Economic conditions; Cambodia -- Economic conditions